PENGARUH PROFESIONALISME KERJA PEGAWAITERHADAP KUALITAS PELAYANAN PUBLIKDENGAN TUNJANGAN KINERJA PADAKANTOR KECAMATAN MEDAN KOTA - Niati lafau Weni; Darmansari lahagu; Elazhari (LPPM Universitas Cipta Mandiri, 2024)
This research aims to determine the effect of employee work professionalism on the quality of public services with performance allowances at the Medan City sub-district office. The research method used is positivistic-based research (concrete data), where the variables are measured using a Likert scale. The data collection method was carried out by conducting field studies, with questionnaires. The population is 25 people. So the number of respondents in this study was 25 respondents, data management used SPSS software, with descriptive analysis and hypothesis testing with simple linear regression analysis. The research results show that there is a positive and significant influence of professionalism on service quality, service quality has a positive and significant influence on benefits. The technique is carried out using Linear Regression Path Analysis which uses a partial t test. It can be concluded that if the P value (sig) < alpha (0.05) then the decision to reject H0, the conclusion of the level test (5%) is sufficient evidence that employee work professionalism (x) influences the quality of public services. service (y). Then, from the linear regression path analysis of employee work professionalism (X) of 0.624 which has a positive sign, it can be concluded that the better the employee work professionalism, the higher the public's satisfaction with service management, resulting in increased facilities and services. infrastructure in order to achieve a symbol of success through the provision of public services